2016
DOI: 10.5858/arpa.2015-0292-oa
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Artifacts and Histopathologic Pitfalls in the Lung

Abstract: Context.-Surgical and pathologic handling of lung physically affects lung tissue. This leads to artifacts that alter the morphologic appearance of pulmonary parenchyma.Objective.-To describe and illustrate mechanisms of ex vivo artifacts that may lead to diagnostic pitfalls.Design.-In this study 4 mechanisms of ex vivo artifacts and corresponding diagnostic pitfalls are described and illustrated.Results.-The 4 patterns of artifacts are: (1) surgical collapse, due to the removal of air and blood from pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 32 publications
1
71
0
Order By: Relevance
“…28 The importance of distinguishing this from artifacts is appreciated by the authors who have published on this topic and criteria are proposed on how to make this distinction. 13, 15, 25 STAS is morphologically different from tissue floaters and contaminant or extraneous tissues that can lead to diagnostic errors.…”
Section: Discussionmentioning
confidence: 99%
“…28 The importance of distinguishing this from artifacts is appreciated by the authors who have published on this topic and criteria are proposed on how to make this distinction. 13, 15, 25 STAS is morphologically different from tissue floaters and contaminant or extraneous tissues that can lead to diagnostic errors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, STAS should be included into pathological reports. However, it is still debatable whether STAS is an in vivo effect in any instances or potentially an artifact induced by cutting though a tumor with a knife (24). Indeed, data from a recent multicenter study in which a defined protocol for macroscopic tumor dissection was applied demonstrate that the number of free tumor cell clusters within air spaces is increased cut by cut (25,26), pointing towards that at least a certain proportion of STAS might be attributed to the processing of unfixed tissue by the pathologist.…”
Section: Stas-fact or Artifact?mentioning
confidence: 99%
“…Thunnissen et al (17) named this phenomenon spreading through a knife surface (STAKS). Blaauwgeers et al (18) performed a prospective, multi-institutional study to confirm the concept of STAKS, and concluded that about 90% of the floating tumor cells and clusters ("STAS") could be explained by mechanical artifacts made by blades/knives.…”
mentioning
confidence: 99%